2011
DOI: 10.2217/pgs.10.188
|View full text |Cite
|
Sign up to set email alerts
|

Systems Pharmacology Assessment of the 5-Fluorouracil Pathway

Abstract: Aim To assess the impact of the 5-fluorouracil (5-FU) drug-pathway genes on cytotoxicity, and determine whether loss-of-function analyses coupled with functional assays can help prioritize pharmacogenomic candidate genes. Materials & methods Dose-response experiments were used to quantify the phenotype of sensitivity to 5-FU following the specific knockdown of genes selected from the 5-FU PharmGKB drug pathway in three human colorectal cell lines. Changes in sensitivity were considered significant if the IC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 38 publications
3
27
0
1
Order By: Relevance
“…Although a further analysis will be needed in patient cohorts with data on detailed drug treatment records, these observations suggested that our PDXGEM predictor could be not only predictive of response to gemcitabine, but could also have a prognostic value in terms of predicting for a long-term outcome OS in patients with PDAC. According to a gene ontology analysis of the biomarkers, the most significantly enriched function was amino acid catabolic process, which is in agreement with that 5-FU drug pathway is regulated via a complex network of anabolic and catabolic genes 35 .…”
Section: Pdxgem For Predicting Response To Gemcitabine In Pancreatic supporting
confidence: 80%
“…Although a further analysis will be needed in patient cohorts with data on detailed drug treatment records, these observations suggested that our PDXGEM predictor could be not only predictive of response to gemcitabine, but could also have a prognostic value in terms of predicting for a long-term outcome OS in patients with PDAC. According to a gene ontology analysis of the biomarkers, the most significantly enriched function was amino acid catabolic process, which is in agreement with that 5-FU drug pathway is regulated via a complex network of anabolic and catabolic genes 35 .…”
Section: Pdxgem For Predicting Response To Gemcitabine In Pancreatic supporting
confidence: 80%
“…Muhale et al [28] showed that UCK2 , along with other genes involved in the 5-FU anabolic pathway, produced a phenotype of cell sensitivity to 5-FU following knockdown. Our stratified analysis using the NKI dataset showed that among patients with stage II breast cancer, chemotherapy significantly improved DFS ( p =0.008) and OS ( p =0.050) in patients with UCK2 -low expression, but not in those with UCK2 -high expression ( p =0.107 for OS and p =0.243 for DFS, respectively), a finding that might be attributed to the sample size of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these genes encode drug resistance enzymes (UMPS; ref. 36) or cell-cycle regulators through P27 function (GFER; refs. 37,38).…”
Section: /Cd24mentioning
confidence: 99%